Predicting long-term disability in a sample of patientes with back pain: A 2-year prospective follow-up study - Esteve-Zarazaga, Rosa; Ramírez-Maestre, María del Carmen; Bendayan, Rebecca; López-Martínez, Alicia Eva; Ruiz-Párraga, Gema Teresa; Serrano-Ibáñez, Elena Rocío (My University, 2015)
The predictive power of the Fear-Avoidance Model is well established although further research is needed on the sequential interrelationships among its variables and the role of resilient factors. This paper presents a 2-year prospective follow-up study with the aim of investigating whether back-pain-related disability was predicted by the following variables which were measured when back pain was acute: the initial level of pain-related Disability; Perceived Pain Intensity; Depression; Fear-Avoidance Beliefs; Anxiety Sensitivity, Resilience and, Experiential Avoidance. With the same aim, two time-variant variables were measured when pain was chronic: Pain Fear-Avoidance and Chronic Pain Acceptance. Methods A sample of 95 patients treated in five primary care centres was assessed five times: when the patients were having an acute back pain episode and at 6, 12, 18 and 24 months. Multilevel regression models were performed via SAS. Results Pain-related Disability over 2 years was significantly predicted by the level of Disability and Fear-Avoidance Beliefs at pain onset, as well as by changes in Pain Fear-Avoidance at the time of the different measurements. Conclusions The results highlighted the predictive power of the Fear-Avoidance Model. According to the results, Pain Fear-Avoidance — composed of Pain Catastrophizing, Pain Vigilance, and Pain Anxiety — significantly predicted Disability over time. Also, initial functional disability played a more prominent role than pain intensity in the transition from acute to chronic pain. These results showed that non-psychopathological fear-avoidance beliefs grounded in the social health culture can account for disability across time.
Keywords: Dolor - Aspectos psicológicos; Chronic Pain; Disability; Fear-avoidance; Prospective study